MENGGALI MAKNA WALASUJI: IMPLEMENTASI NILAI-NILAI TRADISIONAL DALAM PERKAWINAN - Muh Ahsan; Luthfiah Azizah; Rusdaya Basri; Aris (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
This study investigates the application of traditional cultural values embedded in the walasuji symbol within the wedding ceremonies of the Bugis ethnic group, particularly in the Parepare City area. Originally referring to a diamond-shaped protective fence, walasuji has evolved in meaning to become a fruit basket presented as part of the ritual. This tradition is replete with symbols that express noble principles such as loyalty, harmony, responsibility, respect for customary norms, and dedication in establishing a family. However, the philosophical essence of walasuji is increasingly overlooked and viewed merely as a routine procedure in wedding events. This research employs a qualitative sociological approach, utilizing techniques of direct observation, in-depth interviews, and documentary data collection. The findings reveal that the implementation of walasuji values not only strengthens the bond between spouses but also plays a crucial role in preserving local wisdom and Bugis cultural identity. Therefore, it is essential to enhance understanding of the walasuji symbol so that future generations can inherit the noble principles contained within it. Keywords: Walasuji, Traditional Values, Marriage